ISS e o conceito constitucional de serviço de qualquer natureza - Lima, Júlia Silva e (2020)
The present work constitutes an analysis of the meaning of the expression “services of any nature”, provided for in article 156, III, of the Federal Constitution of 1988, listed as object of the tax competence of the Municipalities to impose the tax on services of any nature (ISS). The study involves an examination of the institute of the tax competence and its strict constitutional discrimination, in order to demonstrate that the expression “services of any nature” used in the attribution of municipal tax competence for the imposition of ISS contains a concept and not a type, which implies significant limits to the complementary legislator and the ordinary municipal legislator when listing the facts of the phenomenal world subject to the levy of the tax. In this context, a brief history of the constitutional and legal treatment of the taxation of services in Brazil will be presented, in order to then analyze the constitutional concept of services of any kind, especially what was conventionally called by the doctrine as the “legal” or “civil” and “extra-legal” or “economic” concept of the expression under analysis. The main precedents of the Federal Supreme Court (STF) about the matter will also be presented and analyzed. At last, a definition of the constitutional concept of “services of any nature” for municipal tax purposes will be proposed